Deep brain stimulation programming for intractable obsessive–compulsive disorder using a long pulse width - Beydler, Emily; Katzell, Lauren; Putinta, Kevin; Holbert, Richard; Carr, Brent (Frontiers in Psychiatry, 2023)
Introduction Around 25% of patients with obsessive-compulsive disorder (OCD) do not respond to medication or psychotherapy, producing significant impairment and treatment challenges. Deep Brain Stimulation (DBS) has been shown in multiple blinded trials to be a safe and durable emerging option for treatment-refractory OCD. Intraoperative device interrogation offers a theoretical anchor for starting outpatient DBS programming; however, no definitive post-operative programming algorithm for psychiatrists exists currently. Case Here we present a 58-year-old female with childhood-onset, severe, intractable OCD with multiple failed trials of psychotherapy, medication, and electroconvulsive therapy. After interdisciplinary evaluation, she underwent bilateral electrode implantation targeting the anterior limb of the internal capsule, nucleus accumbens (ALIC/NAc). Intraoperative interrogation afforded sparse information about a preferred lead contact or current density target. Subsequent outpatient interrogation consisted of systematic and independent mapping using monopolar cathodic stimulation with constant current. Modulating bipolar and triple monopolar configurations, amplitude, and pulse width all failed to induce observable effects. Given negligible interrogation feedback, we created an electrical field through the ALIC bilaterally, using the three most ventral contacts to create triple monopoles, with a long pulse width and moderate amperage. Conclusions Three months post-programming, the patient reported significant improvement in OCD symptoms, particularly checking behaviors, with response sustained over the next several months. As with our case, the majority of DBS lead contacts do not induce affective or physiological markers in patients, complicating programming optimization. Here, we discuss an approach to titrating various stimulation parameters and purported mechanisms of physiological markers in DBS for OCD.